Physical Activity Patterns in Lecturers During Covid-19 Pandemic: A Qualitative Study - Mahendro Prasetyo Kusumo (Universitas Muhammadiyah Yogyakarta, 2021)
A sedentary lifestyle has associated with the work of a lecturer. A sedentary lifestyle is one of the Non-Communicable Diseases (NCDs) causes. This study aims to explore physical Activity Patterns in Lecturers during the COVID-19 Pandemic. This study used qualitative research from July to September 2020. Interviews were conducted with sixteen lecturers is divided into two groups. The data collection was through in-depth interview techniques by telephone. Participants were determined by purposive sampling. The number of participants is seventeen. The analyzing data process through transcripts, coding, and determining themes was performed using In-Vivo software. Credibility criteria and triangulation is done to ensure valid data. The results of this study show that the desired pattern of physical activity is to use free time, even though they have difficulty managing time and lack motivation. There is a need for health policy at the university to apply a healthy lifestyle, such as walking between buildings, using stairs, doing independent exercise between working hours, procuring bicycles for transportation between buildings, and maximizing sports facilities management. Conclusion: The physical activity pattern of lecturers mostly utilizes the free time to walk between buildings, go to mosques, and long distances parking to the premises in the university environment.